The polymorphisms influence of some apelin receptor and apelin genes SNPs on the eclampsia pregnancy women's - Khalaf, Mustafa Saleam; Mahdi, Alaa Saleh; Taqi, Rawa M.M. (Edelweiss Applied Science and Technology, 2025)
Eclampsia is a condition that occurs in pregnant women. This condition is associated with genetic and environmental factors that cause changes in the function of the vascular system, placenta, and other components. Genetic polymorphism in the apelin gene may play an important role in the risk of developing eclampsia in pregnant women and also affects the outcome of the birth process. Therefore, the current study aimed to compare the gene polymorphisms of apelin rs56204867 with apelin receptor rs11544374 and investigate their effects on mothers’ and infants' weight gain between the control group of women and the eclampsia group for Iraqi women. This study included the selection of 35 pregnant women suffering from eclampsia and 35 healthy pregnant women of a specific age for the study. The biochemical method PCR–RFLP was applied to both groups to determine the genotype of apelin rs56204867 and apelin receptor rs11544374 gene polymorphisms. The study results showed that according to rs11544374 SNP polymorphisms of apelin receptor genes, TC and TT variant genotypes are significantly associated with eclampsia. On the other hand, this study found that the genotype AA and AG for rs54204867 SNP is higher in healthy women compared with eclampsia women. There is also a significant association between obesity and rs54204867 SNP and rs11544374 polymorphisms in the eclampsia women's group. This study concluded that the rs54204867 SNP polymorphisms of apelin and rs11544374 SNP polymorphisms of apelin receptor genes affect the body weight of the eclampsia women's group because they impact metabolic function, but with specific genotypes. Additionally, these SNP polymorphisms affect blood pressure regulation, leading to elevated proteinuria in the eclampsia women's group.